An ethnomathematical case study on the mathematical concepts, mathematical practices and beliefs of the Malay songket weavers / Nor Maizan Abdul Aziz - Abdul Aziz, Nor Maizan (Institute of Graduate Studies, UiTM, 2016)
Songket is generally valued for its beautiful designs and patterns and not for the originality of ideas, which flows from the creative minds and the skilful hands of the gifted songket weavers. This is a qualitative research on ethnomathematics to investigate the mathematical concepts, mathematical practices and beliefs of the Malay songket weavers. In particular, the mathematics used in the songket weaving process, the motifs and patterns design process and the mathematical concepts found in a few selected songket patterns. Purposive sampling is used to select the subjects of this research. The songket weavers being the subjects for this study fall under two categories; six older generation traditional weavers and three younger generation contemporary weavers. Three mathematics lecturers from Universiti Teknologi MARA were chosen to be the respondents in identifying perceptions on the mathematical concepts that exist in the weaving process and the songket patterns. Questionnaires, observations, semi-structured and unstructured interviews were used to gather the data. The observations and interviews were videotaped and data was analysed using the framework of Universal Integrated Approach. This study has shown that songket weaving not only requires special skill and creativity, but mathematical knowledge and mathematical thinking is also embedded in the creative and artistic minds of the Malay songket weavers…